Effect of Difference Incubation Temperature on The Hatching Time and Hatching Rate of Sinodontis (Synodontis eupterus) Eggs - Amelia Pangreksa; Mustahal Mustahal; Forcep Rio Indaryanto; Bastiar Nur (Jurnal Perikanan dan Kelautan, 2016)
Sinodontis is one of the ornamental fish that have high economic value, because of its unique behavior which could swim in reversed position. The purpose of this study was to determine whether there are differences in the effect of incubation temperature on hatching time and hatching time of sinodontis eggs, and to know the optimal temperature for the time of hatching time and hatching rate of the sinodontis eggs. The main parameters measured were the hatching time and hatching rate of sinodontis eggs. This experiment used completely randomized design with 4 treatment temperature difference, A (25-26oC), B (28-29oC), C (31-32oC) and D (control), with 3 replications. The results showed that the fastest hatching time of sinodontis obtained in treatment C at 1120 minutes (18 hours 40 minutes), then treatment B at 1240 minutes (20 hours 40 minutes), then treatment D at 1340 minutes (22 hours 20 minutes) and longest hatching time in treatment A at 1760 minutes (29 hours 20 minutes). Highest hatching rate of sinodontis obtained in A treatment that was equal to 94.67%, then C treatment that was equal to 82.67%, and treatment D amounted to 81.33% and lowest hatching rate in treatment B 80.00%. Based on the results of the study showed that the optimal temperature to accelerate the sinodontis for hatching time was at a temperature of 31-32oC, while the optimum temperature for increasing the hatchability of sinodontis eggs was at a temperature of 25-26°C.